Inventing a nation Washington, Adams, Jefferson - Vidal, Gore 1925-2012 (Yale Univ. Press, 2003)
"In Inventing a Nation, Vidal transports the reader into the minds, the living rooms (and bedrooms), the convention halls, and the salons of Washington, Adams, Jefferson, and other key figures who helped found the American Republic. Vidal's splendid and percipient prose animates key moments of decision in the birthing of our nation, and we come to know these men in ways we have not until now - their opinions of each other, their worries about money, their concerns about creating a viable democracy. Vidal brings them to life and illuminates the force and weight of the documents they wrote, the speeches they gave, and the institutions of government they fashioned. Above all, Inventing a Nation presents a powerful, compassionate, immensely moving portrait of George Washington, whose resolution, integrity, and intelligence rescued the fledgling Republic many times in its early days."--BOOK JACKET